Towards Marina Gržinić (Ed.), Border Thinking: Disassembling Histories of Racialized Violence - Hristova, Tsvetelina (Identities: Journal for Politics, Gender and Culture, 2019)
Author(s): Tsvetelina Hristova Title (English): Towards Marina Gržinić (Ed.), Border Thinking: Disassembling Histories of Racialized Violence Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 16, No. 1-2 (Summer - Winter 2019) Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 116-118 Page Count: 3 Citation (English): Tsvetelina Hristova, “Towards Marina Gržinić (Ed.), Border Thinking: Disassembling Histories of Racialized Violence,” Identities: Journal for Politics, Gender and Culture, Vol. 16, No. 1-2 (Summer - Winter 2019): 116-118.